IMPROVING STUDENTS’ ACHIEVEMENT IN LEARNING CIVICS THROUGH TEAM GAMES TOURNAMENTS COOPERATIVE LEARNING TYPES AT MTSN 1 ACEH BARAT - Yulidar Yulidar; Cut Anina; Marsita Marsita (FKIP Universitas Al Washliyah Medan, 2019)
The purpose of this study was to improve students’ achievements in learning Civics through Teams Games Tournaments (TGT) cooperative learning type in Year IXC of MTsN 1West Aceh. The method used in this research was an Action Research which consisted of 2 (two) cycles, and each cycle consisted of: Planning, Implementation, Observation, and Reflection. Based on the results of the action research, Teams Games Tournaments (TGT) Type Cooperative Learning can Improve Students’ Achievement in learning Civics in Year IXC of MTsN 1West Aceh. Furthermore, the researcher recommends: (1) Teachers who have the same difficulties can apply Teams Games Tournaments (TGT) Type Cooperative Learning to improve Students’ Achievements. (2) In order to get maximum results, it is hoped that teachers will make Teams Games Tournaments (TGT) Type Cooperative Learning more interesting and varied.